Flexible working in Scottish local authority property: Developing a combined resource management strategy - Khamkanya, Thadsin; Sloan, Brian (International Journal of Strategic Property Management, 2010)
As indicated in Government reports and previous research, the traditional office environment of both central and local governments has been occupied with high occupancy cost. Flexible working supported by information and communication technology, human resource, and workspace management has emerged as a modern concept for managing office resources. Workspace management models covering both activity‐based working area and portfolio flexibility are developed to assist an organisation to allocate staff and working area more flexibly and efficiently. However, public organisations like Scottish Local Authorities (SLAs) are unlikely to fully adopt commercial workspace management models. Therefore, the concept of a combined resource management strategy has been introduced to assist the Authorities in considering adoption in financial/economic terms before taking‐up of flexible working in practice.First published online: 18 Oct 2010